PENGARUH KEBIJAKAN STRATEGIC PATIENCE AMERIKA SERIKAT TERHADAP PROGRAM PROLIFERASI NUKLIR DI KOREA UTARA TAHUN 2010-2016 - Kurnia, Fajar; Rani, Faisal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to reviewing the policy of Strategic Patience by United States toward North Korea. The policy contained was established by Obama Administration which concluded as neither stick neither carrot. The policy is concerned to pursue the North Korea to dismantle all of the nuclear facilities as the precondition of the further talks. However, I analyzed that the policy is a big fail because leaving North Korea behind the full-control of United States even this policy was strenghtened by trilateral cooperation among South Korea and Japan. This policy supported by acumulated sanction by Security Council and United States itself. At my final conclusion of this research, United States was failed to achieved its prominent interest; denuclrization of North Korea.On an academic scope, this research is using the neorealism perspective and the theory of foreign policy. In the scope of theoretical, Forein Policy emphasized the internal problema and internal policy are giving impact to the foreign policy. Indeed, indirectly, Foreign Policy Theory also pursued the comparative study by rolling back policies at the past. By the support of this theory, this research is capable to find out the failures of Strategic Patience.The failure, instead, divided by several factor such as China Factor, the unassertive of the sanctions, the fragile of trilateral, and without neglecting the United Stated miscalculations; which made the circumstances of the failure.United States’ failures on denuclearized North Korea under Obama’s term are the divergent interest inside United Nations Security Council itself. It showed by the renewal of UNSC Resolution 2321 which reflected the China’s interest. Besides, the fail of Strategic Patience can be examined by United States was lacking its power at the region.Keyword: United States, Nuclear Disarmament, North Korea, Strategic Patience, Obama Admnistration.